From Mountain Heights to Basin Depths: The Importance of Thermal Geophysics in Tectonics, Seismology, and Petroleum Geoscience - Kevin P Furlong (Science Faculty of Chiang Mai University, 2019)
Temperature conditions in the crust control many geologic processes. Careful incorporation of the thermal field can provide additional constraints on geologic and geophysical analyses. The basics of crustal and lithospheric thermal structure are discussed and two examples of application of thermal modeling for mountainy building and basin evolution are provided.